Sudden Arrhythmic Death Syndrome: Diagnostic Yield of Comprehensive Clinical Evaluation of Pediatric First‐Degree Relatives. Issue 12 (19th August 2014) - GIUDICI, VALENTINA; SPANAKI, ADRIANI; HENDRY, JENNIFER; MEAD‐REGAN, SARAH; FIELD, ELLA; ZUCCOTTI, GIAN VINCENZO; ABRAMS, DOMINIC; LOWE, MARTIN; KASKI, JUAN PABLO
<x xml:space="preserve">Abstract</x> Aims Sudden arrhythmic death syndrome (SADS) is most often caused by heritable cardiac diseases. Studies in adults have identified evidence of inherited cardiovascular diseases in up to 53% of families, but data on the prevalence of familial disease in children are scarce. The aim of this study was to evaluate the yield of clinical screening in pediatric first‐degree relatives of victims of SADS using a systematic and comprehensive protocol. Methods Patients referred for family screening after sudden cardiac death (SCD) of a family member were, retrospectively, enrolled into the study. Systematic evaluation of the children included clinical examination, family history, electrocardiogram (ECG), echocardiogram, 24‐hour tape, and signal‐averaged ECG. Older patients also underwent exercise testing, cardiac magnetic resonance imaging, and ajmaline provocation testing. Results A total of 90 children from 52 consecutive families were included in the study. An inherited cardiac disease was identified in seven first‐degree children from seven (13.5%) families (five children were diagnosed with Brugada syndrome, one with long QT syndrome, and one with catecholaminergic polymorphic ventricular tachycardia). Two further children had late potentials on signal‐averaged ECGs with no other abnormalities. Conclusions These data show a high prevalence of inherited heart disease in pediatric first‐degree relatives of SADS victims. The results highlight the importance of a systematic, comprehensive approach and ongoing screening of pediatric family members.